Фінансово-правові засоби стимулювання розвитку альтернативної електроенергетики - Молдованов, Д. В.; Moldovanov, D. V. (Право і суспільство. – 2019. – № 5. – С. 198-204, 2019)
Досліджено фінансово-правові засоби стимулювання розвитку альтернативної електроенергетики. Виокремлено такі фінансово-правові засоби подолання загроз у сфері альтернативної енергетики: стимулювання, створення сприятливих умов і фінансових важелів. Розглянуто такі стимули, як «зелений» тариф, зелені сертифікати, аукціони та кредитування. Зроблено висновки щодо доцільності чи недоцільності розроблення та впровадження засобів та їхнього впливу на фінансову систему держави. In the fnancial sphere of Ukraine there are many threats that directly aﬀect the state security of the state. Since the fnancial sector is very large, we have decided to consider one of its areas of inﬂuence. Thus, this article explores the fnancial and legal means of stimulating the development of alternative electricity. Considering the fnancial sphere, it can be noted that one of its functions is to provide for the needs of the public in those services that cannot be provided by enterprises in the normal way. In order to create the necessary conditions for the fulfllment of this function, a fnancial mechanism has been created, with the help of which state regulation of particular branches, in particular alternative energy, is carried out. Based on the structural features of the fnancial mechanism in the feld of alternative energy, we have identifed several tools for overcoming threats in the feld of alternative energy. As scientists propose many options for classifying this mechanism, we have focused on what is provided in the legislation, thereby preventing the distortion of the normative basis. Thus, the following fnancial and legal means of overcoming threats in the feld of alternative energy were identifed: stimulation, creation of favorable conditions and fnancial leverage. Only the incentive system, as broader and more widespread, was taken for analysis. Incentives such as “green” tariﬀs, green certifcates, auctions and lending are considered, but this is not an exhaustive list of funds, so, given the allowable scope of the study, the most important and the most important ones were identifed. In establishing these tools, we proceeded from their chronological evolutionary establishment, both in the legislation of Ukraine and in the European legislation. In addition, conclusions were drawn as to the expediency or impracticality of the development and implementation of funds and their impact on the fnancial system of the state. It is stated which of them can increase investment processes, but at the same time causing damage to the fnancial system, and therefore to the budget of Ukraine in particular. The study provided the characteristics of each tool and provided a brief summary summarizing all the positive and negative features of the tool. Исследованы финансово-правовые способы стимулирования развития альтернативной электроэнергетики. Выделены такие финансово-правовые способы преодоления угроз в сфере альтернативной энергетики: стимулирование, создание благоприятных условий и финансовых рычагов. Рассмотрены такие стимулы, как «зеленый» тариф, зеленые сертификаты, аукционы и кредитование. Сделаны выводы о целесообразности или нецелесообразности разработки и внедрения способов и их влияния на финансовую систему государства.
Молдованов, Д. В. Фінансово-правові засоби стимулювання розвитку альтернативної електроенергетики / Молдованов Д. В. // Право і суспільство. – 2019. – № 5. – С. 198-204. - DOI: https://doi.org/10.32842/2078-3736-2019-5-1-32.
Keywords: Фінансове право. Бюджетне право. Банківське право. Financis Law. Budget Law. Banking Law. Финансовое право. Бюджетное право. Банковское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Економічні науки. Економічна безпека. Economics. Economic Security. Экономические науки. Экономическая безопасность; фінансово-правові засоби; финансово-правовые способы; financial and legal means; альтернативні джерела енергії; альтернативные источники энергии; alternative energy sources; кредитування; кредитование; lending; стимулювання; стимулирование; stimulation